Exercise-Based Rehabilitation to Improve Extremity Muscle Strength in Stroke Survivors: A Study at H. Abdul Manap Regional Hospital (2022–2024) - Howir Riyelma, Gina; Lailan; Rina Nofri Enis; Patrick William Gading; Tia Wida Ekaputri (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Background: Exercise therapy is a medical rehabilitation intervention to increase upper and lower extremity muscle strength in post-stroke patients. Objective: This study aims to determine the characteristics of stroke patients at H. Abdul Manap Jambi Regional Hospital in 2022–2024, including age, gender, and history of comorbidities (hypertension, diabetes mellitus, dyslipidemia). In addition, this study identifies muscle strength before and after exercise therapy and analyzes the effect of therapy duration on increasing muscle strength. Methods: This study is an observational analytic study with a cross-sectional approach. Secondary data were obtained from medical records of stroke patients at H. Abdul Manap Jambi Regional Hospital from 2022 to 2024. The sample consisted of 52 patients who met the inclusion and exclusion criteria. Data analysis used the Paired Sample T-test or Wilcoxon test based on the normality test. Results: Exercise therapy significantly increased upper and lower extremity muscle strength after exercise therapy (p <0.05). Most patients experienced improvement on the Manual Muscle Testing (MMT) scale, especially in the lower extremities, with a dominant increase from scores 2 to 3 and 4. Conclusion: Exercise therapy significantly increases upper and lower extremity muscle strength in post-stroke patients. Therefore, it can be recommended in rehabilitation to optimize motor function recovery.